The Relationship between Energy and Macronutrient Intake and Nutritional Status in Chronic Renal Failure Patients with Haemodialysis - Yoga, M. Agung Prasetya Adnyana; Susmalini, Susmalini; Zuraida, Reni; Indriani, Yaktiworo; Sayekti, Wuryaningsih Dwi (Indonesian Journal of Global Health Research, 2024)
Patients with end-stage renal disease, especially those receiving HD treatment, often show characteristics in the body's protein and energy storage, called protein energy wasting (PEW). HD is the mainstay of treatment for end-stage renal disease and the number of patients undergoing HD is increasing every year. Appropriate nutritional therapy is needed to improve nutritional status and improve the patient's quality of life. Malnutrition is a common condition in patients undergoing haemodialysis (HD) and is associated with increased morbidity and mortality. The main aim of this study was to evaluate the relationship between energy and macronutrient intake and nutritional status in HD patients at at Haemodialysis Unit Dr. H. Abdul Moeloek General Hospital Bandar Lampung. This research is an observational analytical study with a cross sectional design with 30 respondent with chronic kidney failure who underwent HD at at Haemodialysis Unit Dr. H. Abdul Moeloek General Hospital Bandar Lampung from April to May 2024, sampling technique using consecutive sampling technique. Information regarding eating patterns was collected using the 1 x 24 hour food recall method, mini mental status examination (MMSE) used to evaluate dementia in elderly respondents and the nutritional status index was based on an assessment using the mid-upper arm circumference percentile, the patient's height was obtained by measuring the patient's knee height which was then calculated using the Chumlea equation to obtain ideal body weight. The nutritional status index uses mid-upper arm circumference to categorize patients with good and poor nutritional status. Data were analyzed using Fisher's test. The results showed that the majority of respondents had inadequate energy intake as many as 20 patients (66.7%), inadequate protein intake as many as 24 patients (80%), inadequate fat intake as many as 26 patients (86.7%) and inadequate carbohydrate intake as many as 23 patients (76.7%). So it can be concluded that there is no relationship between energy intake (p = 0.633), protein (p = 0.656), fat (p = 0.557) and carbohydrates (p = 0.567) with nutritional status in HD patients at at Haemodialysis Unit Dr. H. Abdul Moeloek General Hospital Bandar Lampung. Further research needs to be carried out to determine the intake of other nutrients such as fluids, sodium and potassium as well as the duration of HD which is a common problem in HD patients.